UNBOXING ENTREPRENEURSHIP: ENHANCING YOUR PRICING STRATEGY KNOWLEDGE - Simatupang, Apriani; Hutabarat, Moses. L. P.; Arianto, Radityo; Gea, Fikra Wini; Kereh, Regina Ferosali Majesty (LPPM Univ. Ibn Khaldun Bogor, 2025)
In an increasingly competitive business environment, understanding pricing strategy has become one of the key elements for entrepreneurial success. The Community Service Program (PkM) titled